Peningkatan Keterampilan Sosial Siswa Melalui Penerapan Pendekatan Auditory Intellectualy Repetition Dalam Pembelajaran Fisika - Yennita '; M. Rahmad; Sugino ' (Jurnal Pendidikan, 2011)
This study aims to describe students' social skills through cooperative learningmodel with Intellectually Auditory Repetition (AIR) approach. Research subjects were 30eight-grade students of junior high school. Twelve students from the two groupsof them wereobservedby using social skills instrument.The students'social skills are comprised of fiveaspects, namely in the task, encouraging participation, taking turns and sharing tasks, activelylistening and asking questions. Data were analyzedusing percentage of every aspect ofstudents' social skills. Based on analysis of data obtained, 91.67 percent students are in highcategory and 8.33 percentin middle category of social skills level. Thus, the application ofcooperative learning model with intellectually auditory repetition in the learning of sciencephysics can develop social skills of junior high school students.